Design And Development Of A Web-Based Employee Leave Information System At PT. Nusa Promosindo - Irvani Arazzy, Riyan; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2023)
Leave is a right of every employee where they can be absent from work for a certain period of time which is usually used by employees for refreshing, family gatherings, illness, childbirth and others. PT. Pilar Nusa Promosindo is a company engaged in the field of printing. At this company, the application for leave is still done manually by filling out a paper formula which is considered inefficient and takes quite a long time. To overcome these obstacles, an online leave application was created which aims to make it easier for employees to apply for their leave. This application uses PHP as the programming language and also uses MySQL as the database. With this application, it is expected to be more comfortable at work because of the ease of applying for leave and monitoring the remaining time off.